2013
DOI: 10.1371/journal.pgen.1003217
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Signaling in the Blood–Brain Barrier Is Required for Male Courtship in Drosophila

Abstract: Soluble circulating proteins play an important role in the regulation of mating behavior in Drosophila melanogaster. However, how these factors signal through the blood–brain barrier (bbb) to interact with the sex-specific brain circuits that control courtship is unknown. Here we show that male identity of the blood–brain barrier is necessary and that male-specific factors in the bbb are physiologically required for normal male courtship behavior. Feminization of the bbb of adult males significantly reduces ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 54 publications
(71 reference statements)
2
24
0
Order By: Relevance
“…Given that sex differences exist in many tissues throughout the fly [45][46][47][48][49][50][51][52][53][54][55], we wanted to determine the anatomical focus of bmm's effects on the male-female differences in triglyceride homeostasis. bmm is highly expressed in the fat body, and previous studies have demonstrated a central role for this tissue in the regulation of triglyceride storage and breakdown in males [29,32].…”
Section: Bmm Function In the Somatic Cells Of The Gonad Plays A Role mentioning
confidence: 99%
“…Given that sex differences exist in many tissues throughout the fly [45][46][47][48][49][50][51][52][53][54][55], we wanted to determine the anatomical focus of bmm's effects on the male-female differences in triglyceride homeostasis. bmm is highly expressed in the fat body, and previous studies have demonstrated a central role for this tissue in the regulation of triglyceride storage and breakdown in males [29,32].…”
Section: Bmm Function In the Somatic Cells Of The Gonad Plays A Role mentioning
confidence: 99%
“…This has been shown for the Drosophila liver and adipose tissue equivalent (the fat body), showing that male courtship behavior can be altered by changing the sex identity of the fat body cells (Lazareva et al, 2007 ). This technique was recently applied to the BBB, showing a behavioral impact of sex-specificity in the BBB (Hoxha et al, 2013 ). BBB-specific, ectopic expression of a gene that feminizes cells ( TraF ) led to reduced courtship behavior in males.…”
Section: Future Questions and Emerging Areas Of Bbb Researchmentioning
confidence: 99%
“…BBB-specific, ectopic expression of a gene that feminizes cells ( TraF ) led to reduced courtship behavior in males. Hoxha et al ( 2013 ) showed that this was not solely a developmental effect, as BBB-specific expression of TraF only during the adult stages of the fly still reduced courtship in males. The authors also showed that this reduction in courtship behavior required the GPCR Moody, which Bainton et al ( 2005 ) previously showed to have separable roles in maintaining BBB integrity (a structural role) and behavioral drug responses (a signaling role).…”
Section: Future Questions and Emerging Areas Of Bbb Researchmentioning
confidence: 99%
“…Factors that mediate these sex-dependent differences in hypothalamic neurogenesis have not yet been identified but could involve numerous levels of regulation, such as hormone-dependent plasticity (de Seranno et al 2010), differences in blood-barrier access between the sexes (Hoxha et al 2013), and hormonespecific induction of feeding behavior (Sieck et al 1978). Lastly, it is possible that it is the survival of newborn neurons, rather than (or in addition to) their proliferation, that is sexually dimorphic, as has been previously demonstrated for prenatally generated hypothalamic neurons (Waters and Simerly 2009;Forger et al 2004;Tobet and Hanna 1997;Park et al 1998).…”
Section: Discussionmentioning
confidence: 99%